Clinical characteristics of vitamin D deficiency rickets in infants and preschool children - Kyoung Huh; Mi Kyeong Woo; Jung Rim Yoon; Gyu Hong Shin; Myoung Jae Chey; Mi Jung Park (Korean Pediatric Society, 2010)
Purpose : Vitamin D deficiency rickets is a significant public health problem that results from insufficient exposure to sunlight and inadequate vitamin D supplementation. The purpose of this study is to identify the clinical characteristics of vitamin D deficiency rickets in infants. Methods : Data of 35 infants diagnosed as vitamin D deficiency rickets at Sanggye-Paik Hospital, Seoul, Korea, from March 2007 to May 2009 were reviewed. Children with plasma 25-hydroxyvitamin D levels<15 ng/mL and 15-30 ng/mL were considered to have vitamin D deficiency and vitamin D insufficiency, respectively. Results : Thirty-five infants (22 boys, 13 girls) were diagnosed with rickets. Mean age at diagnosis was 7.4¡?#?.1 ;months (range: 0.1-29.8 months). Eighteen infants (51%) were vitamin D deficient and seventeen infants (49%) were insufficient. Twenty-eight of all (80%) diagnosed as subclinical rickets. Twenty-nine infants (83%) were below the age of 12months. Twenty infants (57%) had breastfed and ten infants (29%) had iron deficiency anemia. Nine of breastfed infants (45%) were vitamin D deficient and ten of their mothers were vitamin D insufficient. Overall, radiographic evidence of rickets was present in 93% of the cases. Radiographic sign of rickets was evident even in vitamin D insufficient state. Conclusion : It is important for the clinician to screen for subclinical vitamin D deficiency rickets in inadequately supplemented infants by pairing 25-hydroxyvitamin D levels with wrist radiographs. A nationwide epidemiological study of vitamin D deficiency rickets must be conducted and evidence-based national guidelines must be defined to prevent rickets.